ANALISIS AUDIT DELAY DAN SISTEM PENGENDALIAN INTERNAL ISO 50001 TERHADAP KINERJA PERUSAHAAN PT. INDUSTRI KARET DELI - Tuti Nirwan Dewi Sabari Laia; Muhammad Reza Septriawan; Muhamm Andi Prayogi (Worksheet : Jurnal Akuntansi, 2023)
Audit Delay is the length of time it takes for the audit to be completed by the auditor as measured by thedifference in time between the implementation date and the audit report. Audit delay can also bemeasured from the implementation schedule and the realization of the audit conducted by the auditor.The internal control system within the company includes the organizational structure, methods, and allmeasures that are coordinated to protect the company's assets, monitor the accuracy and reliability ofaccounting data, help efficiency and encourage compliance with company management policies.Company performance is a view of the overall condition of the company over a certain period of time,which is the result or achievement that is influenced by the company's operational activities in utilizingits resources. The research was conducted with secondary data types and sources. The data collectionmethod was carried out by conducting data processing and written interviews. Audit delay and internalcontrol systems have a significant impact on the sustainability of the company's energy managementsystem, with energy management aimed at reducing and controlling energy consumption, helping toincrease production, employee productivity, reduce risk, save the environment and costs. Avoidingaudit delays and supervising the internal control system will provide opportunities for energy savings,so that PT Industri Karet Deli's energy performance can achieve its targets and generate profits for thecompany. The conclusions and suggestions of this study are expected to provide information regardingthe average audit delay, so that the auditor can control these factors, management can be firm inmaking decisions regarding audit delays that occur in the energy management system and it isadvisable to plan field work properly so that the process the audit is carried out effectively andefficiently and can follow procedures in accordance with the provisions set by the company'smanagement.